(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2018)
Along the last forty years, since the 78 Constitution was approved, Spain has improved enormously in the eradication of violence against women. Our country is an international reference due to its commitment, legal framework, data collection and institutions & public resources involved in combating gender based violence. Now seen as a real «State issue», after the parliamentary approval of the State Agreement on this matter (on the 28th of September 2017) there are important challenges as figures are still alarming. Reaching legal equality between men and women does not mean that real inequality does not exist any more. Too often, discrimination of women ends up attacking their basic human rights, such as physical and psychological integrity or life.